2020
DOI: 10.1111/bju.14974
|View full text |Cite
|
Sign up to set email alerts
|

Use of a trizonal schema to assess targeting accuracy in prostatic fusion biopsy

Abstract: Objectives To describe the use of a novel 'trizonal' biopsy schema in which 'near‐target' biopsies are taken adjacent to the MRI lesion, in addition to target and systematic biopsies, to determine the accuracy of prostate MRI fusion systems. Participants and Methods A trizonal biopsy technique was used to evaluate 75 men with small Prostate Imaging Reporting and Data System (PI‐RADS) 3–5 MRI lesions (<15 mm) identified from a prospective cohort of 290 men undergoing multiparametric magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Furthermore, all patients within our study cohort who had a positive mpMRI underwent targeted and systematic biopsy. It has been shown that the combination of systematic and targeted biopsy and biopsies around the target lesion should strongly be considered as the best available approach for those with positive mpMRI [5,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, all patients within our study cohort who had a positive mpMRI underwent targeted and systematic biopsy. It has been shown that the combination of systematic and targeted biopsy and biopsies around the target lesion should strongly be considered as the best available approach for those with positive mpMRI [5,43].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional methods of PSA testing and biopsy have resulted in the overdiagnosis of lowgrade prostate cancer without improving detection of highgrade prostate cancer [1,2]; therefore, there has been an increased use of multiparametric MRI (mpMRI) for prostate cancer as it has been shown to reduce the number of patients needing to undergo biopsy whilst improving detection of significant prostate cancer [3]. However, the combination of mpMRI and targeted biopsy reduces the diagnosis of lowgrade prostate cancer but still misses a portion of significant cancer [4,5]. Urologists must therefore combine clinical characteristics with mpMRI to determine which patients should have further investigation with prostate biopsy [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the proportion of men diagnosed by transperineal biopsy increased (38% in 2017 compared with 24% in 2015). We anticipate further increases in transperineal biopsy given the benefits of reduced post‐biopsy sepsis, a severe adverse event sometimes seen after TRUS biopsy [2]; pending proposed changes to the Medicare Benefits Scheme to ensure it is adequately reimbursed; and availability of services. At the time of diagnosis, men most commonly receive a pathological International Society of Urological Pathology (ISUP) grade group of 1–2 (57% in 2017), a proportion that has remained constant since 2015.…”
Section: Figmentioning
confidence: 99%
“…This could include additional GGG of margin comparisons that we have not identified, such as GGG 2 vs 3-5. Current practice is also being shaped by greater adoption of targeted biopsies of the prostate using techniques such as multiparametric MRI of the prostate, fusion biopsy and transperineal biopsies [40]. Compared to transrectal biopsies, more clinically significant prostate cancer is detected in the anterior lobe with the use of transperineal biopsy [41].…”
mentioning
confidence: 99%
“…Compared to transrectal biopsies, more clinically significant prostate cancer is detected in the anterior lobe with the use of transperineal biopsy [41]. Although not formally assessed, these targeted approaches will likely influence the surgeon's approach to RP to achieve negative surgical margins, hence would need to be considered in future studies to better reflect contemporary practice [40,41]. In addition, we expect and encourage further long-term studies exploring not only BCR but other oncological outcomes, particularly systemic progression, cancer-specific mortality and overall survival.…”
mentioning
confidence: 99%